2008
DOI: 10.1016/j.cognition.2007.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a non-linguistic distinction between singular and plural sets in rhesus monkeys

Abstract: Set representations are explicitly expressed in natural language. For example, many languages distinguish between sets and subsets (all vs. some), as well as between singular and plural sets (a cat vs. some cats). Three experiments explored the hypothesis that these representations are language specific, and thus absent from the conceptual resources of non-linguistic animals. We found that rhesus monkeys spontaneously discriminate sets based on a conceptual singularplural distinction. Under conditions that do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…The outcome was determined by the inappropriate singular/plural opposition. Interestingly, it has been shown recently that monkeys, like children, have a dedicated singular/plural distinction that seems separate from other numerical distinctions (Barner, Wood, Hauser, & Carey, 2008). This finding supports the view that the homophony of the numeral ''un" and the indefinite article in French causes children to mistakenly treat an exact number problem as a singular/plural problem.…”
Section: Introductionmentioning
confidence: 63%
“…The outcome was determined by the inappropriate singular/plural opposition. Interestingly, it has been shown recently that monkeys, like children, have a dedicated singular/plural distinction that seems separate from other numerical distinctions (Barner, Wood, Hauser, & Carey, 2008). This finding supports the view that the homophony of the numeral ''un" and the indefinite article in French causes children to mistakenly treat an exact number problem as a singular/plural problem.…”
Section: Introductionmentioning
confidence: 63%
“…However, unlike previous studies, the objects (pingpong balls) were fixed with glue to a small presentation board, to ensure that they moved as a united set. Apparently, Gestalt cues like common fate are taken by infants as cues to set membership (Wynn, Bloom, & Chiang, 2002; see also Barner, Wood, Hauser, & Carey, 2008, for similar evidence from non-human primates). Recent studies by Feigenson and colleagues suggest that other perceptual cues, such as color, shape, and the spatial segregation of objects may also lead infants to treat objects as members of sets (Feigenson, under review).…”
Section: Discussionmentioning
confidence: 95%
“…In the above studies, the individuals move independently of each other, encouraging the infants to deploy parallel individuation. If sets of objects move as coherent wholes (e.g., glued to a platform, such that the items move together), young infants and rhesus macaques distinguish singletons from sets of more than one and fail to distinguish among plural sets of different numerosities, at least for small sets (e.g., 2, 3, 4, and 5; Barner, Wood, Hauser & Carey, 2008; Barner, Thalwitz, Wood & Carey, unpublished data). Again, we do not know why monkeys and infants do not draw on analog magnitudes on these tasks, but the data indicated that they do not, whereas their pattern of behavior reflects a categorical distinction between singletons, on the on hand, and pluralities, on the other.…”
Section: A Third Innate System Of Representation With Numerical Contementioning
confidence: 99%